ECOLOGICAL FEATURES OF NEMATODES OF PLANTS OF THE WESTERN ZARAFSHAN MOUNTAIN RANGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides an ecological analysis of perennial plant species nematodafauna growing in the biocenoses of the West Zarafshan mountain range. The study identified 121 species of nematodes and analyzed the ecological characteristics of these species in the highlands of the mountain. The identified species are divided into groups of pararizobionts, eusaprobionts, devisaprobionts, mycohelminths and parasitic nematodes.